2003
DOI: 10.1177/0886260503255550
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Marital Violence Following Treatment for Alcohol Dependence

Abstract: The impact of an intensive, individually based, partial hospitalization treatment for alcohol dependence on alcohol use, marital violence, psychological abuse, and marital satisfaction among 24 heterosexual male patients and their partners was assessed. Patients received 5 to 6 days of substance abuse treatment in a partial hospital. Patient and partner assessments were conducted at baseline and 6- and 12-month follow-up. Results revealed decreased alcohol use in patients and significant declines in husband-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 67 publications
7
63
1
2
Order By: Relevance
“…Recently, there have a number of reports that suggest treatment for alcohol dependence is associated with reductions in intimate partner violence (O'Farrell & Choquette 1991;O'Farrell et al 2003;Stuart et al 2003), that this reduction is also apparent for verbal aggression (O'Farrell et al 2000) and that this reduction is observable up to 2 years post-treatment (O'Farrell et al 1999). In addition, this research has demonstrated that alcoholics who relapsed did not reduce their violence, whereas alcoholics in remission did reduce their violence (O'Farrell & Murphy 1995).…”
Section: Alcohol and Intimate Partner Violence: When Can We Say That mentioning
confidence: 86%
“…Recently, there have a number of reports that suggest treatment for alcohol dependence is associated with reductions in intimate partner violence (O'Farrell & Choquette 1991;O'Farrell et al 2003;Stuart et al 2003), that this reduction is also apparent for verbal aggression (O'Farrell et al 2000) and that this reduction is observable up to 2 years post-treatment (O'Farrell et al 1999). In addition, this research has demonstrated that alcoholics who relapsed did not reduce their violence, whereas alcoholics in remission did reduce their violence (O'Farrell & Murphy 1995).…”
Section: Alcohol and Intimate Partner Violence: When Can We Say That mentioning
confidence: 86%
“…Violence victimization may also negatively impact substance abuse treatment outcomes (Farley, Golding, Young, Mulligan, & Minkoff, 2004), although there is evidence to suggest that treatment for substance abuse alone or for COD may reduce both IPV victimization and perpetration in the posttreatment year (Maiden, 1997;O'Farrell, Fals-Stewart, Murphy, & Murphy, 2003;O'Farrell, Van Hutton, & Murphy 1999;Stuart et al, 2003). Moreover, studies examining the effect of dual treatment of substance abuse and IPV have found that IPV may be reduced when addressed in the context of substance abuse treatment and supplemented by behavioral couples therapy (Fals-Stewart, Birchler, & Kelley, 2006;FalsStewart, Kashdan, O'Farrell, & Birchler, 2002;Fals-Stewart, O'Farrell, & Birchler, 2001;O'Farrell, Murphy, Stephan, FalsStewart, & Murphy, 2004;O'Farrell et al, 1999;Stuart, 2005).…”
Section: Substance Abuse Treatment Outcomesmentioning
confidence: 98%
“…Los resultados han puesto de manifiesto que la intervención estándar para las adicciones, en pacientes drogodependientes con problemas asociados de violencia contra la pareja, provoca una disminución importante en las conductas violentas, a pesar de no intervenir específicamente en este ámbito Stuart et al, 2003). En el estudio de O'Farrell et al (2003), por ejemplo, con una muestra de 301 hombres alcohólicos, la presencia de violencia contra la pareja disminuyó del 56% antes del tratamiento al 25% después del mismo, a pesar de no haber recibido una intervención específica para ello.…”
Section: Violencia Y Tratamiento De Las Drogode-pendenciasunclassified